281 Surgical results of abdominal versus minimally invasive radical hysterectomy for cervical cancer in San Borja clinical hospital Santiago of Chile. (13th November 2020) - Ibacache, J; Lagos, A; Altamirano, R; Nazzal, O; Solari, M; Pincheira, E; Rojas, L; Cervantes, P; Suarez, E
Abstract : Hospital San Borja Arriaran, Chile Upon the publication of the LACC study, increasing evidence has emerged regarding the superiority of open versus minimally invasive surgery (MIS) in the treatment of cervical cancer. Introduction to report and compare the surgical results among woman undergoing surgery for cervical cancer with open versus MIS in San Borja Arriarán Hospital. Methods retrospective analysis, involving patients with stage IA1 (lymphovascular invasion), IA2, or IB1 cervical cancer undergoing open or MIS between 2015 to 2019. Data obtained from oncology committee registry. Analysis of demographic, histological and surgical variables. Data analyzed using the Chi2, Student's t, and Fischer test with a 95% confidence interval and a P value of <0.05. Results: 42 patients analyzed, 20 in the open surgery and 22 MIS group. The mean age (46.2 ± 2.9 v/s 46.9 ± 2.37; P = 0.49). Surgical result, the number of nodes obtained in open surgery was significantly higher than in the MIS technique (27.4 ± 2.6 v/s 20.3 ± 2.04; P = 0.038), with no differences in the number of positive nodes, compromise of surgical margins, parametrial compromise, tumor size or in lymphovascular invasion. There was no significant difference in adjuvance treatment. Due to the short follow-up period in the open surgery group, no recurrence or survival analysis was performed. Conclusion: Despite the small sample size, a significant difference in known variables of the oncological result, such as the number of lymph nodes obtained. This provides a first approach regarding oncological outcome. Survival analysis will be evaluated in future analysis.